Dampak Penerapan Kebijakan Pemerintah terhadap Eksternalitas Sampah Plastik di Kota Jayapura - Tanan, Christina Irwati; Duri, Jimmi Ari; Tamanbali, Dwi Utari (Fakultas Ekonomi Universitas Samudra, 2021)
This study aims to determine government policies and their impact on plastic waste management in Jayapura City in 2017-2020. The study was conducted at the Environmental and Cleanliness Office. Using qualitative data analysis methods, the study involved 230 community respondents. The results indicate that the majority of the public consider the Jayapura City government's policy on plastic waste management to have been able to reduce the amount of plastic waste. However, there are still many community members who think that the provincial government has not been able to fully reduce the amount of plastic waste, and believe that the policy is not able to reduce plastic waste in the city. Based on the results obtained, it is hoped that this policy can also be applied in traditional markets so that it can further reduce the use of plastic bags and reduce plastic waste in Jayapura City.